The one eaudiobook - Marrs, John (Dark Future, 2018)
***Over 1M Copies Sold!*** Now on Netflix! The USA Today bestseller A Wall Street Journal Best Science Fiction Book of 2018 "Just try to put this gripping thriller down once you pick it up." — AARP "A shock on every other page." — Wall Street Journal How far would you go to find The One ? A simple DNA test is all it takes. Just a quick mouth swab and soon you'll be matched with your perfect partner—the one you're genetically made for. That's the promise made by Match Your DNA. A decade ago, the company announced that they had found the gene that pairs each of us with our soul mate. Since then, millions of people around the world have been matched. But the discovery has its downsides: test results have led to the breakup of countless relationships and upended the traditional ideas of dating, romance and love. Now five very different people have received the notification that they've been "Matched." They're each about to meet their one true love. But "happily ever after" isn't guaranteed for everyone. Because even soul mates have secrets. And some are more shocking than others... A word-of-mouth hit in the United Kingdom, The One is a fascinating novel that shows how even the simplest discoveries can have complicated consequences. Don't miss other suspenseful reads from John Marrs (you'll never see the twists coming!): The Marriage Act The Vacation The Family Experiment The One